Material characterization of GPX®: A versatile in situ solidifying embolic platform technology - Stewart, Russell J.; Sima, Monika; Karz, Jessica; Jones, Joshua P. (Frontiers in Bioengineering and Biotechnology, 2023)
Endovascular embolization is a minimally invasive procedure during which blood flow to targeted tissues is selectively occluded. The list of clinical indications for embolization continues to expand. Liquid embolic agents are injectable compositions that transition into a solid or semi-solid form when introduced into blood vessels. The mechanism that triggers the liquid-to-solid transition is a key distinguishing feature of liquid embolic agents. GPX is a waterborne liquid embolic agent comprising oppositely charged polyelectrolytes: polyguanidinum and inorganic polyphoshate. In situ solidification is driven by electrostatic condensation of the polyelectrolytes, triggered by ionic strength differentials. We report preclinical characterization of the material properties of GPX, it's in vivo effectiveness in acute animal studies, and its potential for chemoembolization. The viscosity of GPX can be varied over a wide range by adjusting the polyguanidinium MW and/or concentration. Formulation of GPX with either tantalum microparticles (30 wt%) or iodinated radiocontrast agents (300 mgI ml-1) did not significantly change the flow behavior of GPX; the viscosity was independent of shear rate and remained within a clinically practical range (80-160 cP). Formulation of GPX with doxorubicin substantially increased viscosity at low shear rates and resulted in a power law dependence on shear rate. High contrast and effective vascular occlusion were demonstrated in both swine kidneys and rete mirabile. Contrast from iodinated compounds was temporary, dissipating within hours. The doxorubicin in vitro release profile was linear over 90 days. The results demonstrate that GPX is a versatile liquid embolic platform that can be formulated with a wide range of viscosities injectable at clinically practical flow rates, with either transient or permanent contrast, and that can provide prolonged zero-order delivery of doxorubicin to embolized tissues.